Omar Calabrese: a classic on the neo-baroque - Leone, Massimo (E|C, 2020)
Neo-baroque: a Sign of the Times by Omar Calabrese (1987) was proposed as a very original attempt to develop a semiotic analysis of culture at a precise stage of its development. This complex, multiform, multi-layered, multi-layered book was disruptive at the time, in the semiotic culture of the time and, more generally, in the human and social sciences landscape, for several reasons.